Reductions in alcohol and cocaine use following a group coping intervention for HIV-positive adults with childhood sexual abuse histories. - Meade, Christina S; Drabkin, Anya S; Hansen, Nathan B; Wilson, Patrick A; Kochman, Arlene; Sikkema, Kathleen J (Addiction (Abingdon, England), 2010)
Few interventions exist to reduce alcohol and non-injection drug use among people living with HIV/AIDS. This study tested the effects of a coping group intervention for HIV-positive adults with childhood sexual abuse histories on alcohol, cocaine and marijuana use.
Keywords: Adaptation, Psychological; Adolescent; Adult; Alcohol Drinking; Child; Child Abuse, Sexual; Cocaine-Related Disorders; Female; HIV Infections; Humans; Intention to Treat Analysis; Linear Models; Logistic Models; Male; New York City; Outcome Assessment (Health Care); Psychotherapy, Group; Sexual Behavior; Stress, Psychological; Substance-Related Disorders; Treatment Outcome; Urban Population